Farmer-To-Farmer Extension (F2FE) approach for speedier dissemination of agricultural technologies: A review - SAH, UMA; SINGH, S K; PAL, JEETENDRA K (The Indian Journal of Agricultural Sciences, 2021)
Enhanced efficiency of extension efforts targeted towards facilitating uptake of newer agricultural technologies byfarmers is much sought after by extension systems all over the world. Experimentation with several methodologieshas been done world over to achieve the said objective. Farmer-to-Farmer Extension (F2FE) approach is a farmer ledapproach that leverages the informal channels of technology penetration in form of existing social networks for diffusionof well proven agricultural technologies in the farming community. The approach emphasizes on experimentationwith newer technology by progressive farmers, followed by sharing of learning gained with other members in thecommunity. The basic strength of this model is the high credibility assigned by the farming community on localinformation source. The approach has well practiced in different forms in developing countries in Asia, Africa andLatin America. The article reflects on experiences gained from experimenting with F2FE approach in different formsand its institutionalization by extension systems across the globe.